Pengaruh Struktur Modal, Likuiditas, Profitabilitas, Firm Size Dan Kepemilikan Institusional Terhadap Nilai Perusahaan Pada Perusahaan Subsektor Retail Trade Di BEI Periode 2017-2021 - Thomas Firdaus Hutahaean; Cynthia Cynthia; Sabrina Sabrina; Lydia Lydia; Hotma Mentalita (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In order to ascertain how the company value in the retail trade company subsector on the IDX will change over the 2017–2021 period depending on variables such as capital structure, liquidity, profitability, firm size, and institutional ownership is the aim of this study. The population of this study is the Retail Trade sub-sector companies on the IDX totaling 30 companies. Six companies were included in the study sample because they applied a purposive sampling technique. The statistical method applied in this study is multiple linear regression analysis. The data shows that institutional ownership, liquidity, and capital structure are influencing factors, while profitability and firm size have little effect on firm value. Moreover, it simultaneously confirms that factors such as institutional ownership, liquidity, profitability, firm size, and capital structure all have a large impact on firm size. Keywords: Capital Structure, Liquidity, Profitability, Firm Size, Institutional Ownership, Firm Value